(untitled) (Revista científica Olimpia, 2020)
A Diploma in Social Studies of physical activity and sport is presented, which facilitates the specialized training of university graduates of Physical Culture of Granma who work in the different spheres of action with the aim of raising their knowledge and skills, as well as their competence and professional performance. The Diplomat is made up of a total of 12 courses articulated with each other with topics such as (Preparation of the athlete, Contemporary Physical Education, Sociological Problems of Contemporary Sport, Psychology of Physical Activity and Sport among others), includes the realization of a theoretical work and additional practical.The background of the postgraduate training and improvement in Cuba, its theoretical foundations and its influence in the career of Physical Culture were analyzed, cognitive needs were identified on the social aspects of sport through the application of surveys and interviews aimed at experts and graduates in Physical Culture.